Healthcare workers’ stress and health behaviors: utilization of the stages of change model - Sangmin Kim; Esther Lee; Catherine Zeman; Andrea Carter (Intelektual Pustaka Media Utama, 2022)
Most healthcare workers are not meeting the American heart association’s recommended 150 minutes of physical activity. The purpose of this study was to examine the differences in healthcare workers' stress on their stages of distribution for physical activity using the stages of change model. A volunteer sample of 122 healthcare workers was asked to complete an online 3-page questionnaire measuring their perceived stress and stages of change distribution for their physical activity. The result revealed that there was a statistically significant difference between the level of stress and stage of change distribution for the recommended level of physical activity as determined by one way analysis of variance (ANOVA) F(4, 118)=3.36, p=.012.